Efek Mediasi Nilai Perusahaan pada Pengaruh Biaya Modal terhadap Return Saham di Indonesia - Wishnu Okky Pranadi Tirta; Fitri Ismiyanti (Universitas Airlangga, 2019)
Investing in real assets or financial assets is increasingly becoming the choice for the public, forgetting a return or profit. This research aims to examine the effect of Cost of Capital on Stock Returns through Corporate Valuesas mediating variables in Indonesia during 2013 - 2017. The sample in this study was 780 companies. The method used in this study is regression analysis to see the influence between variables and path analysis to see the mediating effects of intervening variables. The results of this study indicate that the value of the Company can mediate the relationship between the cost of capital and stock return in Indonesia.